Anxiety levels in parents of asymptomatic neonates and young infants referred for echocardiography. (4th July 2022) - Akrivopoulou, Georgia; Fouzas, Sotirios; Gkentzi, Despoina; Galanopoulou, Katerina; Dimitriou, Gabriel; Karatza, Ageliki A.
ABSTRACT: Introduction: Previous studies in children with innocent murmurs have shown that parental concern is common. Methods: We assessed the anxiety levels among parents of asymptomatic neonates or infants up-to 6 weeks referred for cardiologic consultation because of a heart murmur. A six-item short-form of the state scale of the Spielberger State-Trait Anxiety Inventory (STAI) was completed by the parents before and after consultation. Results: The average STAI score decreased from 14.42 ± 4.54 on arrival to 9.69 ± 4.26 after the consultation (p < 0.001). Overall, the parents felt more calm, less tense, less upset, more relaxed, more content and less worried after the consultation (p < 0.001). Multivariable linear regression analysis showed that the STAI score prior to consultation was related to infants age (coefficient β = – 0.172; P = 0.046) and STAI score post consultation was related to the final diagnosis ( β = 0.312; P < 0.001). Conclusion: In conclusion, parents of asymptomatic neonates and young infants with a murmur exhibit moderate levels of anxiety which can be ameliorated after consultation. Parental education in the field is of paramount importance and the role of both paediatric cardiologists as well as primary care physicians is crucial and decisive.